1904
DOI: 10.1007/bf01840606
|View full text |Cite
|
Sign up to set email alerts
|

Über das Fäulnisgift Sepsin

Abstract: Arbeiten aus dem Laboratorium ftir expcrimentelle Pharmakologie zu Stral3burg i. E. 177. ~ber das Fiiulnisgfft Sepsin. "V' on Edwin S. •aust, Privatd0zent. (Mit I Figur im Text und Tafel lI-IV.) I. Einige frtihere Untersuehungen fiber giftige F~ulnisstoffe und das Verhitltnis des Sepsins zu denselben. Durch eine grol~e Anzahl sorgfiiltig an~estellter und ausgeftihrter Tierversuche hat Gaspard 1) als Erster naehgewiesen, dal3 die in faulendcn Fltissigkeiten auftretenden G a s e ftir das Zustandekommen der ehara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1911
1911
1940
1940

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Albeck (9) believed that it belonged in the group of putrefactive poisons. Murphy and Brooks (7) believe that it may be similar to the substance sepsin isolated by Faust (10). It has been suggested that it might resemble the ~-iminazolyl ethylamine of Dale (11).…”
mentioning
confidence: 86%
“…Albeck (9) believed that it belonged in the group of putrefactive poisons. Murphy and Brooks (7) believe that it may be similar to the substance sepsin isolated by Faust (10). It has been suggested that it might resemble the ~-iminazolyl ethylamine of Dale (11).…”
mentioning
confidence: 86%
“…Heubner mentions a number of other substances which act as capillary poisons. These include a number of double salts of heavy metals, belonging to the gold and iron groups, arsenic and the organic bases emetine and sepsine (Faust, 1904). Several of these show, of course, other toxic properties beyond that exercised upon the capillary wall, which latter becomes dominant only when they are introduced in suitable concentration directlv into the blood.…”
Section: A Comparison Between Two Of the Experiments Ofmentioning
confidence: 99%
“…Heubner mentions a number of other substances which act as capillary poisons. These include a number of double salts of heavy metals, belonging to the gold and iron groups, arsenic and the organic bases emetine and sepsine (Faust, 1904). Several of these show, of course, other toxic properties beyond that exercised upon the capillary wall, which latter becomes dominant only when they are introduced in suitable concentration directly into the blood.…”
Section: The Reactions Of Capillaries To Lightmentioning
confidence: 99%